Hardness and wear resistance of roller burnished 316L stainless steel. (2021) - Tugay, Ibrahim Orhun; Hosseinzadeh, Ali; Yapici, Guney Guven
Abstract: This study investigates the effects of roller burnishing on the microstructure, surface microhardness, and wear resistance of 316L stainless steel. Experimental design based on the Taguchi orthogonal array was employed to determine the optimized parameter set for maximizing the burnished surface microhardness. Roller burnishing refined the microstructure beneath the surface and improved the microhardness by 45%. Subsequently, results of reciprocating tribological experiments revealed a significant increase in the wear resistance after the burnishing process.